Distribution characteristics, risks and sources of heavy metals in surface sediments from typical industrial and mining complex area in Southwest China - Shen, Chuan; Huang, Sheng; Huang, Bangqin; Liu, Zongyan; Yi, Zongwang; Tang, Jiang; Yin, Shucen; Zhang, Jinzheng (Frontiers in Environmental Science, 2025)
With the rapid progress of industrialization and urbanization, large amounts of industrial wastewater and mining waste have been discharged into rivers. The problem is especially severe in areas with intensive mineral resource development and hardware manufacturing. Moreover, frequent heavy rainfall and flooding during the flood season significantly increase surface runoff and sediments resuspension, promoting the mobilization and redistribution of heavy metals (HMs) in river systems. Therefore, it is of great practical importance to systematically identify the distribution characteristics and ecological risks of HMs pollution in such regions under changing climatic conditions. Eighty-five surface sediment samples were collected in Southwest China, and the concentrations of As, Hg, Cd, and Pb were determined. The geo-accumulation index (Igeo) and the potential ecological risk index (RI) were used to assess contamination levels and ecological risks, and principal component analysis (PCA) and positive matrix factorization (PMF) were applied to trace pollution sources. The results show that Cd and Hg have similar spatial patterns, with high concentrations mainly downstream of mining areas and industrial parks. Igeo and RI assessments indicate that Hg pollution in sediments is severe in four major rivers of Dazu District, followed by Cd, while As and Pb show relatively low pollution levels. Source apportionment revealed that industrial and traffic-related activities contribute 55.05% of HMs inputs, mining activities account for 41.28%, and natural sources contribute 3.67%. Cd and Pb mainly originate from industrial emissions and traffic, Hg is primarily associated with mining, and As is derived from natural sources.